Assessment of marine water quality index in mangrove estuarine: case study in Setiu River Estuary - Azman, Azid; Mohd Saiful, Samsudin (2018)
This study provides information on marine water quality index in the Setiu River estuary. Mangrove estuarine and river mouth water are classified in Class E in MWQI. The subsequent MWQI with scales among 0 to 100 will define the grouping of the marine water quality from “Excellent” to “Poor”. Six sampling station has been choosing and the sampling activity has been done from July 2016 to January 2017. Post-hoc Tukey HSD test calculates by evaluating whether MWQI for ST1 is more than the critical MWQI value for all relevant pairs of treatments. The test is also performed by using studentized range distribution as well as p-values corresponding to an observed value of MWQI. Continuous monitoring of water quality in mangrove estuarine and river so that it is possible to preserve the quality of mangrove estuarine ecosystem.